PERANAN PLANT CATALYST DAN PUPUK KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea) - Guntoro, W.; PS, Djarwatiningsih; G, Guniarti (Universitas Muhammadiyah Jember, 2017)
Rubbish dump of vegetable market is one of environmental problem in Surabaya city. An effort to process the rubbish become an organic fertilizer (compost) will give a benefit not only overcome the environmental problem but also can use it source of organic fertilizer unproductive land in Surabaya. Many kinds of decomposition technic can use to decompose these rubbish dump such as decomposition vessel shape (rectangular form and prismal form). The technic can combine with EM-4, a degrade microorganism, to decompose the rubbish dump perfectly. Reaserch has a purpose to know the effect of vissel shape and dosage of EM-4 on growth and yield of enclevi plant.The fully randomized design was in the factorial experiment with 3 replications. The first factor was vessel shape : Rectangular shape (B1) and prismal shape (B2). Second factor was dosage of EM-4 : 50 cc EM-4/150 kg rubbish (D1), 100 cc EM-4/150 kg rubbish (D2), 150 cc EM-4/150 kg rubbish (D3), 200 cc EM-4/150 kg rubbish (D4).The result showed there was an interaction between decomposition vessel shape and dosage of EM-4 on variabel number of leaves, leaf width, plant length, wet weighy per plant. The best treatment combination was prismal vessel with EM-4 200 cc/150 kg rubbish (B2D4) on the variabel number of leaves (9,77), leaf width (776,05 cm2), plant length (26,70 cm), and weigth per plant (189 g).